Food insecurity status of rural households during the post-planting season in Nigeria (2013)
About two-thirds of rural households in Nigeria are engaged in crop and livestock production as their main source of livelihood. These households are especially vulnerable to chronic food shortages owing to adverse weather and the unavailability of enough food from home production, especially during the post-planting season. This study attempts a proper empirical identification of the food insecure and the reasons for their insecurity, through a profile of food insecurity indices and an investigation of the factors influencing their status during the post-planting season in rural Nigeria. We construct food insecurity indices and specify a probabilistic model, employing the post-planting visit data of the first wave of the General Household Survey-Panel (2010). Results showed that almost half (49.4 percent) of rural households in the country were food insecure during the post-planting period. Identified key rural food insecurity determinants include: gender of household head, tertiary education of household head, access to both formal and informal credit and remittances, household size, dependency ratio and living in the North-Central, North-East, South-East and South-West Geopolitical zones of the country. Since food availability remained below the required levels for large parts of the rural populace during this season, identified food insecure households should be targeted for safety nets.